A new criterion for determination of coal ash sintering temperature using the pressure-drop technique and the effect of ash mineralogy and geochemistry. (1st September 2016) - Li, Jianbo; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Highlights: A new criterion for determining ash sintering temperature proposed and validated. The new criterion was independent of fuel types and experimental conditions. Ash specific area and pore volume decreased sharply at the on-set of sintering. The new criterion more adequately represents the ash sintering process. Effect of ash mineralogy and geochemistry on sintering systematically studied. Abstract: A new criterion for determining the ash sintering temperature measured using the pressure-drop sintering technique, based on the first-order and second-order derivatives of the pressure drop curves as a function of temperature, was proposed. The new criterion was evaluated against the one widely used in the literature (the old criterion ) by examining the variations in the specific surface area, pore volume and pore size of the ash pellets being sintered as a function of sintering time and temperature for the ashes of three different coals of vastly different mineralogical and geochemical properties. The response of ash sintering temperature determined based on the two criteria to the experimental conditions, namely, the ash pellet compaction pressure and gas flow rate, was also investigated. The effect on ash sintering temperature of the base to acid (B/A) ratio ranging from 0.09 to 4.79 by blending the coals was also determined and evaluated. It was found that sintering temperature determined according to the new criterion was lower than that based on the old criterion. Consistent with the literature findings, the sintering temperature decreased with increasing the B/A ratio. The microstructural analysis confirmed that the ash sintering temperature defined using the new criterion was closer to the temperature of the onset of the sintering process than the old criterion. The ash sintering temperature based on the new criterion was independent of the ash pellet compaction pressure and gas flow rate, while the ash sintering temperature according to the old criterion was subject to the experimental conditions. This implies that the new criterion more accurately captures the onset temperature when the ash sintering occurs and provides an improved means to determine the ash sintering temperature using the pressure-drop technique.